Exceptionally Preserved Setae: A Possible Morphological Synapomorphy of Cambrian Lophotrochozoans - Liang, Yue; Topper, Timothy P.; Holmer, Lars E.; Hu, Yazhou; Liu, Fan; Zhang, Zhifei (Evolution & development, 2025)
ABSTRACT Cambrian Lagerstätten yield exceptionally preserved fossils that have greatly improved our understanding of the origin and evolution of animal groups. Brachiopoda, a phylum of bivalved marine invertebrates nested firmly within the lophotrochozoan protostomes, are widely recovered in such Lagerstätten. The marginal chitinous setae (or chaetae) of brachiopods are the most commonly described soft tissue and have been interpreted as performing a defensive and/or sensory role. Despite their relatively common appearance in Cambrian Lagerstätten, the origin, function, and evolution of setae in the Brachiopoda is poorly known. Here, we document exquisitely preserved setal structures from South China and Laurentia paleocontinents giving new insights into their formation, microstructure and preservation mode. New setae typically make their appearance within the follicle of a neighbouring older seta and then branches off laterally forming its own follicle. Setal microstructure is likely to be composed of many canals, highly comparable to setae of their recent counterparts. Moreover, setae recovered from these palaeo‐continents present different preservation: aside from the normal preservation of iron oxides and carbonaceous ingredients, some compositions of calcium are also detected in this originally chitinous organization. Investigating the evolutionary origins of chitinous setae, a specialized type found notably in lophotrochozoans such as brachiopods and annelids, reveals its presence in early Cambrian stem groups. This character likely serves as a morphological synapomorphy in lophotrochozoan evolution. However, the dearth of morpho‐ultrastructure and comparative studies in Cambrian fossils presents a challenge in fully understanding this evolutionary development. The Lophotrochozoans comprise one of the major groups within the animal kingdom, while the relationships within this group remain unclear. We explored the microstructure and formation of setae and suggest that setae may represent a morphological synapomorphy of lophotrochozoans, which is currently dearth of morpho‐ultrastructure and comparative studies in fossils.